PROSES PENGAJUAN GUGATAN CERAI PADA PENGADILAN AGAMA - Maria Rosalina; Zulkifli AR; Salsabila Azzahra; M. Farhan Tigor Lubis (Universitas Islam Sumatear Utara, 2022)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on God's commandments. However, in practice, in carrying out domestic life, small and large fights often occur, which results in disturbed happiness in the household, even divorce. Other reasons for divorce are infidelity, adultery, irreconcilable quarrels, persecution, not providing a living, jealousy, and in the KHI the reasons for divorce are added, the husband violates taklik talak and changes religion or apostasy. Based on Article 39 Paragraph (1) of the Marriage Law, divorce can only be carried out before a court session, after the court has failed to reconcile the husband and wife. However, many people, such as people in Suka Beras Village, Perbaungan District, Serdang Bedagai Regency, divorce only by saying the words divorce or writing it on stamped paper, not filing for divorce to the court, especially the religious court that applies to people of Islam. This is because many people do not understand the process of filing a divorce suit to the religious court, and assume divorce in Courts will require expensive fees, long administrative procedures, difficult trial procedures and so on, so the PKM team sees it necessary to carry out PKM in Suka Beras Village, Perbaungan District, Serdang Bedagai Regency, with the title Process for Filing Divorce Claims in Court Religion. The method of activity is carried out in the form of Legal Counseling. The results of this PKM are that the Suka Beras Village community understands the process of filing a divorce suit to the religious court, and the conclusion is that the Suka Beras Village community does not understand the Process for Filing Divorce Lawsuits at the Religious Courts, and does not understand the consequences law arising from divorce, and it is necessary to increase Legal Counseling with the same material.